Successful Treatment of Cerebral Venous Thrombosis with Rivaroxaban: A Case Report with Brief Review - Karki, Mohan (Nepal Journal of Neuroscience, 2025)
Cerebral venous thrombosis (CVT) is one of the rarest causes of stroke in general population, where thrombosis occurs in cerebral venous system. Treatment of CVT is mainly done by heparin followed by vitamin K antagonist. Direct oral anticoagulants are introduced which are safe and effective against traditional therapy, however recent protocol do not recommend. A 22 year-male came to emergency department with chief complaints of severe headache, multiple episodes of vomiting and 2- 3 episodes of loose stool for 3 days. He had two episodes of abnormal body movement in emergency department. Computed tomography (CT) scan of head and then CT venography of head also were done after admission that reported venous thrombosis in superior sagittal sinus, bilateral transverse sinus and internal cerebral vein. Patient was admitted and treated with direct oral anticoagulant (rivaroxaban). He was discharged on 8th day of admission without any neurological deficits.